Between Customary and Islamic Law: Financial Inheritance Practices in the Surakarta Sunanate Royal Family - Zuhdi, Syaifuddin; Dimyati, Khudzaifah; Absori, Absori; Wardiono, Kelik; Apreliyanti, Virra Ervita (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2025)
This article aims to analyze the division of inheritance carried out by the royal family of the Surakarta Sunanate in Central Java Province. Data were collected through interviews and observations involving six royal families. The findings show that the descendants of the Surakarta Sunanate royal family divide inheritance based on agreements reached withing the family. Within the royal family, there are two types of inheritance. The first is the king’s personal property, which is divided according to Paugeran (royal customary law), using a ratio of 2:1 between sons and daughters, unless the king has left a testament. The king’s testament, known as sabda pandita ratu, is considered absolute. If the king issues a testament that removes the inheritance rights of a family member, that person’s rights are annulled. This stands in contrast to Islamic law, which limits the scope of a testament to one-third of the estate and prohibits the disinheritance of a rightful heir. The second type of inheritance is palace property, which may only be inherited by the son or heir who succeeds the late king. These practices illustrate the (dis)harmony between Islamic inheritance law and royal customary inheritance law in specific contexts. [Artikel ini bertujuan untuk menganalisis pembagian harta warisan yang dilakukan oleh keluarga kerajaan Kasunanan Surakarta Provinsi Jawa Tengah, Indonesia. Pengumpulan data dilakukan dengan metode wawancara dan observasi terhadap enam keluarga kerajaan keturunan Kasunanan Surakarta. Hasil penelitian menunjukkan bahwa keturunan keluarga kerajaan Kasunanan Surakarta membagi harta warisan berdasarkan kesepakatan yang dilakukan melalui musyawarah keluarga. Dalam keluarga raja, terdapat dua jenis warisan, yaitu harta pribadi raja, yang dibagi berdasarkan Paugeran (hukum adat) dengan perbandingan 2:1 bagi anak laki dan perempuan. Hal ini berlaku kecuali jika raja berwasiat. Wasiat raja yang disebut sabda pandita ratu bersifat mutlak, dimana jika ia menentukan pembagian rata, maka warisan akan dibagi rata. Atau, jika ia berwasiat menghapus hak waris salah satu anggota keluarga, maka akan terhapus. Di dalam hukum Islam, seorang pewaris hanya dapat wasiat maksimal 1/3 dari hartanya dan tidak bisa menghapus ahli waris. Jenis harta kedua adalah harta keraton yang tidak bisa diwariskan secara pribadi kepada semua keluarga raja, namun hanya akan diberikan kepada satu saja ahli waris yang menggantikan mendiang raja. Praktik-praktik ini menggambarkan adanya (ketidak)selarasan antara hukum waris Islam dan hukum waris adat kerajaan dalam konteks tertentu.]